Pengaruh Disiplin Kerja Dan Kompensasi Terhadap Kinerja Karyawan Pada PT Kharisma Cahaya Krisnawan Bogor Jawa Barat - Selti Lesnussa; Hira Maulida (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. The research aims to determine the influence of work discipline and compensation on the performance of employees of PT Kharisma Cahaya Krisnawan Bogor, West Java, this type of research uses a quantitative method. Which is descriptive. The respondents of this study were all employees at PT Kharisma Cahaya Krisnawan Bogor, West Java, with a population of 55 (fifty-five) employees and used questionnaires to collect data from Variables of Work Discipline and compensation and Vaeiabel .performance of employees. The results of the study show that work discipline has a positive and significant effect on employee performance, this is evidenced by the test value of t-t-table 2.478 > ttable 1.674 with a significant level of 0.000 < 0.05, meaning that work discipline (X₁) affects employee performance (Y) and the variable work discipline (X₂) is calculated by 6.326 > ttable 1.674 meaning that work discipline (X₂) affects employee performance (Y). while based on the results of the F test, it was found that the fcal value was 63.729 > ftable 3.16 with a significant level of 0.000 < 0.05. Thus, it can be said that work discipline and work compensation together have a positive and significant effect on employee performance at PT Kharisma Cahaya Krisnawan Bogor West Java.. Keywords: Work Discipline, and Compensation, Employee Performance.